159 Lessons learned initiating a RCT using an approved drug in a new setting (SPRING Study). Issue 6 (27th May 2022) - Grant, Robert; Lessels, Sarah; Jenkinson, Michael; Watts, Colin; Marson, Anthony; Erridge, Sara; Bulbeck, Helen; Chisholm, Eve Macdonald
Abstract : Background: Trials of approved medications for new indications are becoming increasingly common (repurposing). SPRING – Seizure Prophylaxis IN Glioma is a trial of prophylactic Levetiracetam in adults without prior history of seizure versus no AED. Significant delays were encountered in the set up phase. Issues: Legal contracts between Sponsor and NIHR/UCB (£1.76m) were prolonged.UCB (Belgium) would only transfer drug when ethics had been granted and BREXIT loomed. Company to package levetiracetam required national procurement exercise. Conflicting IRAS advice (Ireland, Scotland, England). Inclusion criteria included patients must have capacity. As patients could lose capacity during study this required Adults with Incapacity REC (Essex), secondary review in Scotland and screening for capacity at each visit. MHRA – mandated monitoring for suicidal ideation at each visit, and detail on contraception during study. HRA – suggested changes to the Patient Information Leaflet and a Schedule of Events Cost Attribution Template – requiring multiple substantial amendments. Neurosurgical centres may feed several oncological departments - site contracts are complex. Electronic eCRF takes time to build and test. Conclusions: Consider planning for longer set up phase in grant submissions. Views expressed are those of the author(s) and not necessarily those of the NHS, NIHR or DOHSC. robin.grant@luht.scot.nhs.uk